How Is TikTok #Interreligious? : An Inductive Thematic Analysis - Velasco Morla, Aída (Poligrafi, 2024)
This study analyzes how TikTok allows users to make interreligious practices visible and share them, highlighting the coexistence between different religious traditions. Through the platform, creators showcase scenes of daily coexistence, interreligious events, and mixed ceremonies, while also denouncing the discrimination and disapproval associated with interreligious relationships. Three main themes were developed using inductive thematic analysis: Interreligious Sentimental Relationships (67.9%), Interreligious Experiences (21.8%), and Interreligious Facts and Information (10.3%). The study suggests that TikTok acts as a space for self-representation and interreligious connection through the hashtags #interreligious and #interfaith, overcoming echo chambers and increasing the visibility of interreligious content. The creation of religious content on TikTok materializes faith and expands the individual-group-Sacred interaction to a global environment, where religious practices are shared and reinterpreted.